Progresivitas Hukum Kewarisan Beda Agama di Indonesia Berbasis Keadilan dan Maṣlahah - R Rohmawati (International Journal Ihya' 'Ulum al-Din, 2018)
The Division of the inheritance of the most crucial of them, there is a difference of religion between the heirs and the muwarriṡ, both the difference when muwarriṡ was still alive or when a heir has died. Indonesia, Islamic law as contained in the compilation of Islamic law (KHI), have determined that religious differences can be a hindrance to each other can be inherited. Along with the development of the times, the provision in the KHI was not considered relevant to the needs of today's society, so the necessary progressive efforts to respond to the problem of Islamic inheritance laws in Indonesia. Complexity and plurality of society Indonesia demanding the Islamic jurist to do the renewal of the law, as the religious court judges has been made in resolving the different religious inheritance matters by using the rechtsvinding function justified by positive law and compile Islamic law, when there is no law that governs. The renewal of the law in the form of the granting of the estate to the heirs of muwarriṡ Muslims from non-Muslims and the granting of probate wajibah to non-muslim heirs of muwarriṡ of Islam. This is done for the sake of Justice and benefit of tegaknya in human life.